The Effects of Financial Ratios on The Stock Prices of Digital Banks - Sagala, Timbul Pandapotan; Fadjar, Nurman Setiawan (Contemporary Studies in Economic, Finance and Banking, 2025)
Digital bank stocks are one of the investment options in the capital market. However, most digital banks have volatile stock price movements. In addition, digital banks also have unstable and poor financial capabilities, especially in profitability, activity, and solvency. This study aimed to examine the effect of financial ratios on the stock price of digital banks. This study uses panel data regression with research objects consisting of 7 digital banks listed on the Indonesia Stock Exchange from 2018 to 2023. The results showed that Return On Assets, Total Assets Turnover, and Operating Expenses Operating Income have no effect on the stock price of digital banks. Meanwhile, Debt Equity Ratio has a negative effect and Loan Deposit Ratio has a positive effect on digital bank stock prices. This study is expected to be a reference for making investment decisions in digital bank stocks for investors and can be a reference for making policy directions for digital bank management.   Abstrak Saham bank digital merupakan salah satu opsi investasi di pasar modal. Namun, sebagian besar bank digital memiliki pergerakan harga saham yang fluktuatif. Selain itu, bank digital juga memiliki kemampuan finansial yang belum stabil dan cenderung buruk, khususnya pada profitabiltas, aktivitas, dan solvabilitas. Tujuan penelitian ini adalah meneliti pengaruh rasio keuangan terhadap harga saham bank digital. Penelitian ini menggunakan regresi data panel dengan objek penelitian yang terdiri dari 7 bank digital yang terdaftar di Bursa Efek Indonesia pada tahun 2018 hingga 2023. Hasil penelitian menghasilkan Return on Assets, Total Assets Turnover, dan Beban Operasi Pendapatan Operasi tidak berpengaruh terhadap harga saham bank digital. Sedangkan, Debt Equity Ratio berpengaruh negatif dan Loan Deposit Ratio berpengaruh positif terhadap harga saham bank digital. Penelitian ini diharapkan dapat menjadi referensi pengambilan keputusan investasi saham bank digital bagi investor, serta dapat menjadi referensi pengambilan arah kebijakan bagi pihak manajemen bank digital.